Postpartum depression and brain response to infants: Differential amygdala response and connectivity. (1st November 2016) - Wonch, Kathleen E.; de Medeiros, Cynthia B.; Barrett, Jennifer A.; Dudin, Aya; Cunningham, William A.; Hall, Geoffrey B.; Steiner, Meir; Fleming, Alison S.
ABSTRACT: Recent evidence suggests that postpartum depression is associated with reduced amygdala (AMY) response to negative stimuli. However, given the anhedonic features of PPD, it is important to consider mothers' brain response specifically to positive infant and to other positive stimuli. Mothers with ( n  = 28) and without ( n  = 17) clinically determined PPD ( n  = 28) viewed smiling pictures of infants (Own and Other), and positive non-infant stimuli (Non-Infant). First, we examined group differences in AMY response across conditions. Next, psychophysiological interaction was used to examine group differences in AMY connectivity across conditions. Connectivity estimates were then correlated with measures of maternal mood and anxiety. PPD mothers, compared to non-PPD mothers, showed overall increased AMY response across conditions in the right AMY. Despite this, PPD mothers demonstrated decreased bilateral AMY–right insular cortex (IC) connectivity as compared to non-PPD mothers when they view Own–Other infants. Furthermore, decreasing AMY–IC connectivity was associated with increasing symptoms of depression and anxiety. These differences were evident only for infant stimuli and did not apply to all positively valenced stimuli. Thus, PPD mothers show altered brain response and connectivity in regions strongly implicated in the processing of socially and emotionally relevant stimuli, as well as interoception and the evaluation of subjective emotional experience.